2018
DOI: 10.1016/j.ccell.2018.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Complex Interplay between Epitope Specificity and Isotype Dictates the Biological Activity of Anti-human CD40 Antibodies

Abstract: SummaryAnti-CD40 monoclonal antibodies (mAbs) that promote or inhibit receptor function hold promise as therapeutics for cancer and autoimmunity. Rules governing their diverse range of functions, however, are lacking. Here we determined characteristics of nine hCD40 mAbs engaging epitopes throughout the CD40 extracellular region expressed as varying isotypes. All mAb formats were strong agonists when hyper-crosslinked; however, only those binding the membrane-distal cysteine-rich domain 1 (CRD1) retained agoni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
171
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(182 citation statements)
references
References 50 publications
(104 reference statements)
8
171
3
Order By: Relevance
“…However, it appears that 2 distinct epitopes defined by CD40L/CD154 competitivity lead to an agonistic or antagonistic response at physiological concentrations of FcgR. 52 Thus, mapping the precise site of antibody-antigen binding can help to define the elicited response.…”
Section: Epitopementioning
confidence: 99%
“…However, it appears that 2 distinct epitopes defined by CD40L/CD154 competitivity lead to an agonistic or antagonistic response at physiological concentrations of FcgR. 52 Thus, mapping the precise site of antibody-antigen binding can help to define the elicited response.…”
Section: Epitopementioning
confidence: 99%
“…In support of this, the agonistic LILRB3 mAb did not suppress T cell proliferation in the absence of monocytes. Binding epitopes influence the ability of mAb to modulate receptor function in many systems (35,45) and so it was unsurprising to see LILRB3 mAb capable of differing functions. However, the D4-binding A1 mAb was a strong inhibitor of proliferation; whereas, other D4-binding mAb (e.g., A28) had no significant effect.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, domain-specific epitopes did not seem to correlate directly with LILRB3 mAb-mediated effector cell functions and may not be predictive of LILRB3 mAb function per se. Further detailed analyses, e.g., surface alanine scanning mutagenesis (45) and/or structural studies, are required to define the specific extracellular epitopes engaged by the selected LILRB3 mAb and to investigate their influence on receptor activity.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work studying the mechanisms of action of therapeutic antibodies has shown that the region of the molecule targeted is also an important consideration, with even subtle shifts in binding epitope resulting in large impacts on effector function and efficacy [19,20]. Recent work on several TNFRs has further highlighted the importance of these aspects in influencing the type and strength of effector function [20][21][22][23]. For example, we demonstrated the importance of domain binding on the biological activity of anti-CD40 mAb, showing that membrane distal CRD1binding mAb were strong agonists of CD40 with membrane proximal mAb less potent [22].…”
Section: Introductionmentioning
confidence: 99%